2018
DOI: 10.1080/13813455.2018.1465437
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of cranberry extract and losartan against aluminium chloride-induced hepatorenal damage associated cardiomyopathy in rats

Abstract: The present study was designed to evaluate the effect of cranberry extract (CRAN) and/or losartan (LOS) against aluminium chloride (AlCl) induced hepatorenal damage associated cardiomyopathy in rats. To induce hepatorenal and cardiotoxicity, animals were received (AlCl; 70 mg/kg i.p.) for 8 weeks day after day and treated with CRAN (100 mg/kg b.wt.) orally daily for 4 weeks started after 4 weeks from AlCl injection accompanied with an administration of LOS (5 mg/kg i.p.) three times weekly for 4 weeks. Our dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…So, we found an increase in MDA level with a decrease in the levels of GSH and FRAP. Oxidative stress increased both hepatic and renal MDA with reduction in serum FRAP level as described by Galal . In the same concern, γ‐irradiation of rats caused a significant decrease in FRAP…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…So, we found an increase in MDA level with a decrease in the levels of GSH and FRAP. Oxidative stress increased both hepatic and renal MDA with reduction in serum FRAP level as described by Galal . In the same concern, γ‐irradiation of rats caused a significant decrease in FRAP…”
Section: Discussionsupporting
confidence: 58%
“…Oxidative stress increased both hepatic and renal MDA with reduction in serum FRAP level as described by Galal. 26 In the same concern, γ-irradiation of rats caused a significant decrease in FRAP. 27 Bekheet 14 expressed that when cadmium was co-treated with BPF induced increase in the activity of GSH, SOD and CAT with significant decrease in the level of MDA when compared to cadmium group only.…”
Section: Discussionmentioning
confidence: 96%
“…Because these substances can reduce inflammation, oxidative stress, and gut dysbiosis, they can help people with CRF lead a better lifestyle. Fruits with a rich red color, such as berries, are known to have beneficial bioactive compounds, among others (de Almeida Alvarenga et al, 2018; Mafra et al, 2021), and many studies have shown that the levels of creatinine and urea in the blood were reduced by intake of cranberry (Galal et al, 2019) (Figure 2).…”
Section: Cranberry: a Brief Overviewmentioning
confidence: 99%
“…Some studies recently demonstrated that bioactive compounds contained in cranberries reduced hepatic steatosis by decreasing the production of fatty acids, TNF‐α, Toll‐like receptor 4 (TLR‐4) and NF‐κB (de Almeida Alvarenga et al, 2019; Glisan et al, 2016; Jia et al, 2020; Peixoto et al, 2018; Rodriguez‐Mateos et al, 2016). Galal et al (2019) discovered that cranberry extract (when combined with losartan) decreased hepatotoxicity and cardiotoxicity in rats (Figure 2).…”
Section: Other Potential Benefits Of Cranberry For Human Healthmentioning
confidence: 99%
“…The third, fourth, and fth groups received 75, 100, and 150 doses of cranberry extract and heart-damaging drugs. Then the blood samples were taken and sent to the laboratory on the fourth weekend and a week after nishing the injections in the fourth week (the sixth weekend) to check the serum factors, including cardiac creatine kinase MB (CK-MB), cardiac troponin I (cTnI), and aspartate aminotransferase (AST) [6,10,11].…”
Section: Experimental Designmentioning
confidence: 99%